Beta-1, 4-galactosyltransferase 2 c.909C>T gene variant is predictive of on-clopidogrel platelet reactivity. (18th July 2018) - Pallet, Nicolas; Belleville-Rolland, Tiphaine; Savalle, Anne; Lejeune, Manon; Mauge, Laetitia; Bertil, Sebastien; Loriot, Marie-Anne; Gaussem, Pascale
CYP2C19 genotype influences clopidogrel response but only accounts for a small part of the variability in platelet reactivity. Recently, exome sequencing identified a variant of the gene encoding B4GALT2 as a potential candidate implicated in on-treatment platelet reactivity. Carriers of the B4GALT2 c.909C>T variant have lower platelet reactivity indicating that B4GALT2 could influence clopidogrel sensitivity and could expose to the risk of bleeding events. We undertook this observational retrospective study to determine if B4GALT2 c.909C>T influences P2RY12-specific vasodilator-stimulated phosphoprotein phosphorylation and agonist-induced platelet aggregation in a nonselected cohort of 174 patients under clopidogrel-based antiplatelet therapy. Our results indicate that in individuals under dual antiplatelet therapy, B4GALT2 c.909C>T might be an independent genetic predictor of on-treatment platelet reactivity.